REMUNERATION PAYABLE TO PERFORMERS FOR THE BROADCASTING OF PHONOGRAMS. TYPES OF PHONOGRAMS - Mariana SAVU (Challenges of the Knowledge Society, 2014)
The institution of copyright and related rights, as regulated in our system by Law nr.8/1996, deals with the protection of literary, artistic and scientific works and their creators. By a definition that has a tradition in our doctrine, the legal institution of copyright (generally speaking) means all the legal rules governing social relations that arise from the creation, publication and use of literary, artistic or scientific works. The moral and patrimonial rights of the author and neighboring rights stakeholders are protected both by the special law, mentioned above, and also by the common law provisions. Among them is included the Decree no.31/1954 concerning individuals and legal entities but also the Civil Code. One argued problem during the arbitrations, which take place at ORDA headquarters, institution that provides the Secretariat, also in the courts of law, when setting claims was promoted by Collecting Societies against bad payers users, was to analyze the two phrases commercial phonograms and phonograms published for commercial purposes.